FORMULASI DAN EVALUASI SABUN CAIR EKSTRAK ETANOL DAUN JARAK PAGAR ( Jatropha curcas) SEBAGAI ANTIBAKTERI Staphylococcus aureus - Betania, Putri (Politeknik Tiara Bunda, 2022)
One of the medical plants is Jatropha plant which has good antimicrobial activity for gram negative-positive bacteria. The purpose of this research is to find out the formulation and ability of jatropha leaves extract liquid soap. This type of research is experimental research. working procedures consist of sampling, plant identification; sample processin, extracing, making liquid soap and evaluating liquid dosage form (organoleptic, pH test, high foam, specific gravity). Organolpetic test results of all formulas have a liquid and viscous form. The white base smells like a scented rose, formula 5% wa green, formula 10% was dark brown and formula 15% was dark brown; formula 5%, 10%, 15% special odor of Jatropha leaves. Base pH test 9.7; formula (5%, 10% 15%), 9.6; 9.8;9.5. base foam height tet 61.53 mm, formula (5%, 10% 15%) shich is 70.51mm; 56.81 mm; 76.47 mm. Base specific gravity test 0,79/ml, formula (5%, 10% 15%) namely 1,01g/ml; 1..01g/ml; 1.01g/ml. This study can be concluded that the quality of liquid soap of Jatropha leaves ethanol extract meets the requirements of good liquid soap accordance with the standards set by SNI 06-4085-1996 namely organoleptic tests, pH test, high foam test, and specific gravity test